TIR-domain-containing adaptor protein gene TIRAP S180L polymorphism is not increased in Behcet's disease patients in two ethnic cohorts - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2013)
Objective. The single nucleotide polymorphism (SNP) of TIRAP (Serine 180 leucine, S180L) that is shown to be associated with Behcet's disease (BD) in a European-derived cohort, but not in Middle Eastern patients is investigated in two other populations. Methods. Two cohorts of BD patients and controls from Turkey (n=797) and Italy (n=633) were genotyped by sequence specific primer-polymerase chain reaction (SSP-PCR) or TaqMan q-PCR assays. Results. Genotype and allele frequencies in TIRAP S180L (rs8177374) were not different between BD patients and controls in either ethnicity. Furthermore, a meta-analysis between the Turkish and the Italian BD cohorts did not reveal an association between this non-synonymous SNP in TIRAP and BD (meta-analysis OR=0.94, meta-analysis p=0.61, Q statistic heterogeneity p=0.11). Conclusion. TIRAP S180L gene polymorphism, which was previously shown to be associated with BD in a Caucasian population, has been replicated in either Turkish or Italian population in our study.
Keywords: Behcet's disease; TIRAP; genetic susceptibility; ASSOCIATION; MAL/TIRAP